2015
DOI: 10.1016/j.ijsu.2015.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Medical grade honey in the management of chronic venous leg ulcers

Abstract: A best evidence topic in vascular surgery was written according to a structured protocol. The question addressed was: In patients with chronic venous leg ulcers (CVLU), does the use of medical grade honey as compared to standard wound therapy improve clinical outcomes? A total of 299 papers were identified using the search protocol described, of which five represented the best evidence available to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Honey has been shown to possess antibacterial ( Jenkins et al, 2011 , Nishio et al, 2016 ) and anti-fungal ( Irish et al, 2006 ) effects. Furthermore, several studies showed that honey is capable to heal burn wounds, ( Vandamme et al, 2013 ), chronic venous leg ulcers ( Holland and Norris 2015 ), and foot ulcers in diabetic patients ( Wang et al, 2019 ), suggesting that honey possesses high medicinal value.…”
Section: Introductionmentioning
confidence: 99%
“…Honey has been shown to possess antibacterial ( Jenkins et al, 2011 , Nishio et al, 2016 ) and anti-fungal ( Irish et al, 2006 ) effects. Furthermore, several studies showed that honey is capable to heal burn wounds, ( Vandamme et al, 2013 ), chronic venous leg ulcers ( Holland and Norris 2015 ), and foot ulcers in diabetic patients ( Wang et al, 2019 ), suggesting that honey possesses high medicinal value.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendation for clinical practice and further research Medhi et al (2008)  high efficiency of honey in observational studies (99% of cases completely healed)  RCTs show moderate efficiency of honey (56% of cases completely healed)  some RCTs failed to show higher efficiency of honey as compared with controls  topical application of honey is beneficial in wound healing but larger prospective randomized studies are needed Vandamme et al 2013 honey had wound healing stimulating properties  available evidence for deodorizing and wound pain reducing properties is low  larger and well randomized studies need to be performed Asamoah, Ochieng, Meetoo (2014)  honey is effective in the treatment of diabetic ulcers  however, there is a lack of quality evidence to support and guide clinical practice  more randomized studies need to be performed Tian et al (2014)  honey may be more effective in decreasing overall treatment time  it facilitates debridement  it promotes angiogenesis and granulation tissue formation; it accelerates wound healing  due to a small quantity of published studies, large, multicenter studies are needed Holland, Norris (2015)  smaller RCTs show improved outcomes of honey therapy when compared with standard approaches  larger RCTs show no benefit of honey therapy  future RCTs must examine particular clinical outcomes (time to healing, reduction in pain)  the efficacy of honey in more acute settings should be examined Jull et al (2015)  honey dressings heal burns more quickly than conventional dressings  honey heals acute and chronic wounds more quickly than SSD (low quality evidence)  honey may heal infected post-operative wounds more rapidly than povidone-iodine (low quality evidence)  the effects of honey relative to controls are unclear for venous leg ulcers, diabetic foot ulcers and minor acute wounds (low quality evidence)…”
Section: Resultsmentioning
confidence: 99%
“…As with phages, honey has a long history as an antimicrobial agent and has been shown to target multiple bacterial pathogens, inhibit biofilm formation, and may increase wound healing [ 127 , 128 , 129 , 130 , 131 ]. The broad antimicrobial properties of honey stem from the presence of hydrogen peroxide [ 132 ], a high sugar content, and the presence of methylglyoxal (MGO) and the antimicrobial peptide bee defensin-1 [ 133 ].…”
Section: Increasing Antibacterial Activity and Host Rangementioning
confidence: 99%